2019
DOI: 10.3390/cancers11070901
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Translatability of “Identified” Circulating miRNAs for Diagnosing Breast Cancer: Overview and Update

Abstract: The effective management of patients with breast cancer (BC) depends on the early diagnosis of the disease. Currently, BC diagnosis is based on diagnostic imaging and biopsy, while the use of non-invasive circulating biomarkers for diagnosis remains an unmet need. Among the plethora of proposed non-invasive biomarkers, circulating microRNAs (miRNAs) have been considered promising diagnostic molecules because they are very stable in biological fluids and easily detectable. Although the discovery of miRNAs has o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 87 publications
(118 reference statements)
1
25
0
Order By: Relevance
“…As reported in Figure 2, 14% of selected studies reported miR-155 as a tissue-deregulated miRNA associated with BC, whereas 3% of studies associated its circulating deregulation with BC. Although the non-specificity of miR-155 in human cancers was previously found in our study [7], the highest number of studies associating miR-155 with BC (14%) suggests its potential role as a tissue biomarker. However, circulating miR-155 seems to have a better role as a biomarker of pancreatic cancer (26%) than of BC (3%).…”
Section: Hmdd Databasesupporting
confidence: 46%
See 2 more Smart Citations
“…As reported in Figure 2, 14% of selected studies reported miR-155 as a tissue-deregulated miRNA associated with BC, whereas 3% of studies associated its circulating deregulation with BC. Although the non-specificity of miR-155 in human cancers was previously found in our study [7], the highest number of studies associating miR-155 with BC (14%) suggests its potential role as a tissue biomarker. However, circulating miR-155 seems to have a better role as a biomarker of pancreatic cancer (26%) than of BC (3%).…”
Section: Hmdd Databasesupporting
confidence: 46%
“…MiRNAs are useful tools for diagnostic and prognostic purposes in several diseases [40]. In recent years, many studies have investigated the clinical value of miRNAs in BC [7,41], a worldwide public health problem that poses significant challenges in terms of disease management. To date, miR-155 represents one of the most studied miRNAs in different human pathologies, including BC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, several recent studies have shown that microRNAs (miRNAs) can provide a potential diagnostic and therapeutic approach for human breast cancers including estrogen-receptor negative breast cancers [34][35][36]. Moreover, circulating miRNAs can be used as a non-invasive tool for early diagnosis and provide a new avenue for estrogen-receptor negative breast cancer management [37]. In this review we will summarize the recent advances made in the identification and role of estrogen-receptor negative specific circulating miRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…However, miRNAs have not been applied in clinical practice because of inconsistencies in the selection of specific miRNAs for diagnostic and prognostic purposes, methodological challenges, patient heterogeneity, and differences in genetic background, sex, age and metabolic status. 9 miRNA-21 has been described as one of the most significantly upregulated miRNAs in human breast cancer and other neoplasms, such as gastric, colorectal, pancreatic, lung and ovarian carcinomas. [10][11][12] In addition, its expression has been associated with tumor diagnosis and development as well as poor prognosis.…”
Section: Introductionmentioning
confidence: 99%